One-step synthesis of photoluminescent nanofluids by direct loading of reactively sputtered cubic ZrN nanoparticles into organic liquids - Protsak, Mariia; Biliak, Kateryna; Nikitin, Daniil; Pleskunov, Pavel; Tosca, Marco; Ali-Ogly, Suren; Hanuš, Jan; Hanyková, Lenka; Červenková, Veronika; Sergievskaya, Anastasiya; Konstantinidis, Stephanos; Cornil, David; et al. (Nanoscale, 2024)
ZrN nanofluids may exhibit unique optoelectronic properties because of the matching of the solar spectrum with interband transitions and localized surface plasmon resonance (LSPR). Nevertheless, these nanofluids have scarcely been investigated, mainly because of the complexity of the current synthetic routes that involve aggressive chemicals and high temperatures. This work aims to validate reactive dc magnetron sputtering of zirconium in Ar/N as an environmentally benign, annealing-free method to produce 22 nm-sized, highly crystalline, stoichiometric, electrically conductive, and plasmonic ZrN nanoparticles (NPs) of cubic shape and to load them into vacuum-compatible liquids of different chemical compositions (polyethylene glycol (PEG), paraffin, and pentaphenyl trimethyl trisiloxane (PTT)) in one step. The nanofluids demonstrate LSPR in the red/near-IR range that gives them a bluish color in transmittance. The nanofluids also demonstrate complex photoluminescence behavior such that ZrN NPs enhance the photoluminescence (PL) intensity of paraffin and PEG, whereas the PL of PTT remains almost invariable. Based on DFT calculations, different energetic barriers to charge transfer between ZrN and the organic molecules are suggested as the main factors that influence the observed optoelectronic response. Overall, our study provides a novel approach to the synthesis of transition metal nitride nanofluids in an environmentally friendly manner, deepens the understanding of the interactions between ZrN and organic molecules, and unveils new optoelectronic phenomena in such systems.